Comparison of panel cointegration tests - Deniz Dilan Karaman Örsal (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2007)
The main aim of this paper is to compare the size and size-adjusted power properties of four residual-based and one maximum-likelihood-based panel cointegration tests with the help of Monte Carlo simulations. In this study the panel-p, the group-p, the panel-t, the group-t statistics of Pedroni (1999) and the standardized LR-bar statistic of Larsson er al. (2001) are considered. The simulation results indicate that the panel-t and standardized LR-bar statistic have the best size and power properties among the five panel cointegration test statistics evaluated. Finally, the Fisher Hypothesis is tested with two different data sets for OECD countries. The results point out the existence of the Fisher relation.
Keywords: C23; C33; C15; 330; PanelCointegration tests; Monte Carlo Study; Fisher Hypothesis; Panel; Kointegration; Fisher-Effekt; Schätzung; Theorie; OECD-Staaten